The treatment of paremias in the Italian translation of Arturo Pérez-Reverte's Los perros duros no bailan - Sardelli, Antonella Maria (Romanica Olomucensia, 2024)
This paper deals with the treatment of paremias in the Italian translation of Arturo Pérez-Reverte's Los perros duros no bailan (Hard dogs don't dance). All the paremias found in the Italian translation were extracted and compared with the forms present in the source text. Then a reflection on the paremiological correspondences in Italian was carried out on the basis of the extrinsic analysis of the paremias, with special attention to the functions that some of the sententious utterances play in the text and to the presence of de-automatised paremias. The comparison of the source text and the target text with regard to the paremias under study led to the identification of four literal correspondences, one conceptual correspondence, and five literal translations. In addition, eight deautomatised paremias (including four in Latin) and two pseudo-paremias were detected. The result is a TT that may well be exemplary of the multitude of techniques and strategies that can be applied in phraseological and paremiological translation. Literal and conceptual correspondences, which, in principle, are not so difficult to locate when working with related languages, do not always constitute the best equivalence of a sententious utterance inserted in a literary text.
Keywords: paremias; literature; translation; Spanish; Italian; Arturo Pérez-Reverte